Ecommerce Strategy Towards Shopee Consumer Behaviour In Online Shopping Through Electronic Word Of Mouth (EWOM) Variables - I Gusti Made Oka Astana (International Journal of Social Science and Business, 2021)
The growing use of internet-based technologies provides enterprise E-commerce with transformative benefits. The success of E-commerce is determined by the behavior of sellers and their decisions about which platform to use between application-based E-commerce or social media. Online shopping through the internet supports consumers to find information about a product or service and make purchases through direct interaction with online retailers. Word of mouth plays an essential role in consumer behavior, especially in online marketing, which supports consumers seeking more references. This study aims to analyze the effect of E-commerce and electronic word of mouth (EWOM) on consumer behavior in online shopping. The study was conducted on 75 respondents, and researchers used SmartPLS 3.0 to examine the relationship between variables in the model through SEM. From the research results obtained, internet marketing strategies directly affect EWOM and consumer behavior, while EWOM also directly affects consumer behavior. E-commerce startups have the most significant direct positive influence on online shopping consumer behavior across all channels. This result means that Shopee should give prime attention to its E-commerce strategy to increase its consumers.